Factors Affecting Talent Management towards Gen Y - Ismail, Fadillah; Mardhiyah Nor Aziz, Ainul; ati Norazman, Irmaw; Anisah Atab Yaakoub, Siti (International Journal of Engineering and Technology, 2018)
Talent management within organization is a human resource strategy that seeks to develop and retain talented and potential employee. Talent management among Gen Y has obtained critical enthusiasm for the organization. The research objective for this study is to develop conceptual framework of factors affecting talent management among Gen Y in organizations. Gen Y was chosen as the concentration of this investigation in relationship between factors affecting talent management (globalization, knowledge economy, changing the world work, demographic changes, and technology) and talent management. This study enhances to the new challenges and fulfill critical gap that now exists in organization. Thus, this research is important to academia and managerâ€™s level to develop talent management and human resource strategy in the organizations.Â